Antioxidative responses of Cocos nucifera against infestation by the Red Palm Weevil (RPW), Rhynchophorus ferrugineus, a new invasive coconut pest in Malaysia - Norhayati Y.,; Wahizatul Afzan A.,; Siti Noor Jannah S.,; Nurul Wahidah M.R., (Penerbit Universiti Kebangsaan Malaysia, 2016)
Interaction between the Red Palm Weevil (RPW) and coconuts will stimulate the plants’ early response by producing the reactive oxygen species (ROS) which causes lipid peroxidation and membrane damage of the host plants. Thus, a multiple defense lines, including both scavenging enzymes and molecular antioxidants have been evolved to promptly inactivate these radicals. This study investigated the responses of catalase (CAT), peroxidase (POD), ascorbate peroxidase (APX), α-tocopherol, ascorbic acid and carotenoids contents of three coconut cultivars which were PANDAN, MAWA and MATAG against the RPW infestation. The infested PANDAN and MAWA exhibited higher CAT, POD and APX specific activities of 2.60 ± 0.11, 5.0 ± 0.72 and 1.58 ± 0.20 units/mg protein for PANDAN whereas 1.13 ± 0.04, 39.38 ± 2.29 and 1.15 ± 0.16 units/mg, protein for MAWA) compared with controls. However, MATAG cultivar showed no significant difference (p<0.05) in the production of both enzymes except for POD specific activities. RPW infestations only managed to trigger the α-tocopherol concentrations in the MAWA cultivar compared with the others. Infested MAWA and MATAG increased the ascorbic acid concentrations, however, a contrast results was observed in infested PANDAN. All coconut cultivars exhibited higher carotenoids content (2771.20 ± 263.90, 3043.20 ± 526.35 and 921.20 ± 281.10 μg/g.fwt of PANDAN, MAWA and MATAG, respectively) compared with their respective controls (455.20 ± 135.10, 1408.40 ± 103.02 and 248.80 ± 110.39 μg/g.fwt). The above results indicated that the oxidative stress induced by the RPW infestation would stimulate the activities of enzymes and molecular antioxidants studied especially in infested MAWA. Thus, it may be suggested that MAWA cultivar was more tolerance towards RPW infestation compared to MATAG and PANDAN. It is hoped that this finding will provide clues on how plant respond toward stress during infestation, thus further action can be activated as soon as possible to control the spread of R. ferrugineus.